IMPLEMENTASI GERAKAN LITERASI UNTUK PENANAMAN PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR DI SD NEGERI JAKENAN - Marina Puspita Wati; Sri Surachmi; Sri Utaminingsih (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed at: 1. Revealing the implementation of the literacy movement at SD Negeri Jakenan, 2. Knowing the instilling of students’ characters formed in the literacy movement at SD Negeri Jakenan, 3. Knowing the reasons why the literacy movement was held at SD Negeri Jakenan. This type of research was qualitative research. The setting of this research was SD Negeri Jakenan Pati, and the object was the students’ behavior at SD Negeri Jakenan Pati. This research found that the school literacy movement aiming to cultivate the character of elementary school students at SD Negeri Jakenan, one of which was to carry out reading habits before teaching and learning activities began. This activity lasted for between 10 to 15 minutes each day. This activity was coordinated by the principal of the school and teachers. The characters shaped from the implementation of this activity were responsibility, fond of reading, respect for achievement, curiosity, and religion. Based on this research, it was suggested that teachers should be role models for students since teachers were very influential in the success of instilling students’ character. Then, the institutions should pay more attention to literacy activities by providing more books and programs that supported students' interest in reading.